Comparative associations between anticholinergic burden and emergency department visits for anticholinergic adverse events in older Korean adults: a nested case-control study using national claims data for validation of a novel country-specific scale - Sunghee Hwang; Jee Eun Chung; Kwanghee Jun; Young-Mi Ah; Kwang-Il Kim; Ju-Yeun Lee (BMC, 2021)
Abstracts Background Considering the limited generalizability of previous anticholinergic burden scales, the Korean Anticholinergic Burden Scale (KABS) as a scale specific to the Korean population was developed. We aimed to validate the KABS by detecting the associations between high anticholinergic burden, measured with the KABS, and emergency department (ED) visits compared to the pre-existing validated scales in older Korean adults. Methods A nested case-control study was conducted using national claims data. The cases included the first anticholinergic ED visits between July 1 and December 31, 2016. Anticholinergic ED visits were defined as ED visits with a primary diagnosis of constipation, delirium, dizziness, fall, fracture, or urinary retention. Propensity score-matched controls were identified. Average daily AB scores during 30 days before the index date were measured. Multivariate logistic regression analyses were performed. Results In total, 461,034 were included. The highest proportion of those with high AB was identified with KABS (5.0%). Compared with those who had a KABS score of 0, older adults with a score ≥ 3 were at higher risk for overall anticholinergic ED visits (aOR, 1.62, 95% CI, 1.53-1.72), as well as visits for falls/fractures (aOR: 1.54, 95% CI: 1.40-1.69), dizziness (aOR: 1.44, 95% CI: 1.30-1.59), delirium (aOR: 2.96, 95% CI: 2.28-3.83), constipation (aOR: 1.84, 95% CI: 1.68-2.02), and urinary retention (aOR: 2.13, 95% CI: 1.79-2.55). High AB by KABS showed a stronger association with overall anticholinergic ED visits and visits due to delirium and urinary retention than those by other scales. Conclusions In conclusion, KABS is superior to pre-existing scales in identifying patients with high AB and predicting high AB-related ED visits in older Korean adults.